Nuclear lncRNA stabilization in the host response to bacterial infection. (22nd June 2018) - Munschauer, Mathias; Vogel, Jörg
Abstract : Long non‐coding RNAs (lncRNAs) play important roles in many cellular pathways, but their contribution to the defense of eukaryotic cells against pathogens remains poorly understood. A new study from Imamura et al in The EMBO Journal reports that Salmonella infection in human cells impacts nuclear RNA decay, which in turn drives the accumulation of otherwise unstable nuclear lncRNAs, some of which may have protective effects against this common bacterial pathogen. These unexpected findings demand more efforts to fully decrypt the molecular functions of lncRNAs in innate and adaptive immunity. Abstract : Salmonella infection impairs the nuclear RNA decay machinery in human cells, increasing the abundance of long non‐coding RNAs with a role in innate immunity.